Briquetes produzidos de engaço de uva como alternativa para geração de energia - Oliveira, Laura Hoffmann de (2020)
The global energy matrix is mainly concentrated in non-renewable sources, however, this scenario is constantly renewing, in the sense of making renewable sources as the main energy sources. Agricultural and forest biomass are found in nature in large volumes, using them in materials that are capable of adding economics, energy quality and social responsibility are fundamental to society's demand. A technique widely used in rural areas and as a way to use residual biomass is the briquetting process, numerous investigations portray the possibility of using agricultural waste to replace and add to the raw materials commonly used in heat generation. The wine sector is one of the most important for the Brazilian agricultural economy, providing means of subsistence for small and medium producers, however, a large amount of waste is generated after the processing of the grape, giving prominence to the stalk, the woody cluster where the grape grains. Information regarding the energetic potential of this material is still rare in the literature. Therefore, with the interest of studying this residual biomass with ways to apply it in the generation of heat, the present work aimed to evaluate the quality of briquettes produced with grape stalks. The study was divided into two stages, where the first consisted of the chemical and energetic characterization of the residual biomass and the second in the evaluation of the granulometry effect on the physical and mechanical properties of briquettes. The work was developed at the Federal University of Santa Maria, the stages of chemical analysis carried out according to TAPPI standards, the briquettes were made in a laboratory briquetting plant, in the Forest Products Laboratory, the grape stalk was homogenized and dried at room temperature until approximately 11% moisture, 40 g of biomass were used for each briquette, divided into four treatments with seven repetitions, in different granulometries. The results obtained indicate through descriptive statistics that the grape stalk has chemical and energetic properties that potentiate it as energy biomass for heat generation, the lignin fractions (28.91%), total extracts (32.27%) and fixed carbon (21.17%) provide subsidies that it is a material that can be used as densified material. The particle size of the grape stalk influenced the physical-mechanical properties of the briquettes, the smaller the granulometry, the better the accommodation of the material, making it more resistant and with greater density, ensuring that briquettes produced with the residual biomass of viticulture are materials quality and with advantages in terms of storage and transport.